Essence and Specific Features of State Regulation in the Field of Air Transport - О. V. Brusakova (Bulletin of Kharkiv National University of Internal Affairs)
The emphasis has been placed on the fact that an important direction in the development of air transport infrastructure is the increase of the efficiency of state regulation in the field of aviation transport. The author has analyzed the existing scientific approaches to the interpretation of the terms of “state regulation”, “state management”, “public management”, “public administration”, “legal regulation”; has revealed the peculiarities of their relationship. It has been argued that state regulation, state management and public administration are interrelated legal categories that differ in the object of management (regulation), purpose, forms and methods of implementation of management (regulatory) measures, as well as the range of entities authorized to implement these measures. It has been substantiated that state regulation is a process implemented by various branches of government by available legal means in order to ensure regulatory impact on the relevant social environment, focused on creating conditions for effective operation of entities and facilities in areas desirable and useful for certain industries. and the state in the whole.